Water Measurement for Agricultural Irrigation and Drainage Systems - Brian Boman; Sanjay Shukla (EDIS)
Circular 1495, an 11-page illustrated publication by Brian Boman and Sanjay Shukla, gives equations and examples for measuring depth and volume of water, describes several devices and techniques for measuring flow. Published by the UF Department of Agricultural and Biological Engineering, October 2006.